Physical Properties of Basmati Varieties of Paddy - Patel, N.; Jagan, S. K.; Jha, S. K.; Sinha, J. P.; Kumar, Amrender (Journal of Agricultural Engineering, 2014)
Physical properties of two varieties (PB1 and PB1121) of basmati paddy were determined at moisture contents ranging between 22.5 and 9.5% (w.b.). Moisture content was found to have significant effect on the properties of both the varieties. Axial dimensions, sphericity and surface area of both varieties decreased with decrease in moisture content. The thousand grain mass, bulk density and angle of repose decreased from 27.83 to 19.72 g, 378 to 322 kg.m-3 and 48.54 to 30.06 degrees, respectively while true density and porosity increased from 1266 to 1298 kg.m-3 and 70.17 to 75.19%, respectively, with decrease in moisture content in PB1. In case of PB1121 variety, the corresponding values were 29.94 to 22.24 g, 464 to 429 kg.m-3, 36.06 to 28.06 degrees, 1366 to 1398 kg.m-3 and 60.03 to 69.31%, respectively. Terminal velocity and coefficient of friction decreased with decrease in moisture content, while hardness of paddy increased.